Effect of roselle (Hibiscus sabdariffa L.) on serum lipids of Sprague Dawley rats - Tee, Pau‐Ling; Yusof, Salmah; Mohamed, Suhaila; Umar, Nor Aimi; Mohamed Mustapha, Noordin (2002)
The efficacy of roselle as a functional food has been revealed lately, especially for its antioxidant bioactivity. In this study, the benefits of roselle were further studied in vivo using the model of male Sprague Dawley rats fed with normal diets (C), 2.5 percent roselle (R), 2.5 percent roselle with 15 percent soybean oil (RO) and 15 percent soybean oil (O) for 25 weeks. The results demonstrated that supplementation of roselle in the diets significantly (p < 0.05) reduced the gross body weight and increased the highdensity lipoproteins cholesterol (HDLC) compared to the rats fed with normal diets and oil diets, and reduced the level of triglycerides in the serum. Serum total cholesterol of R group decreased compared to C but increased in RO compared to O group. Significant increase (p < 0.05) of serum uric acid was observed in R group at week 15 and 20. Addition of roselle in oil diet significantly decreased (p < 0.05) the malondialdehyde formation at week 20 and 25 but there was no significant effect of roselle on the catalase activity among the treatments at all time points. Suggests that roselle might play a role in the prevention of atherosclerosis and obesity. © 2002, MCB UP Limited